Code switching among teachers and students in an ESL classroom / Sarasvathy Annandarajah - Sarasvathy, Annandarajah (2014)

(untitled)
English is a compulsory subject, which is taught as a second language (ESL) in Malaysian classrooms. Despite the Ministry of Education and school principals’ instructions against code switching in the ESL classrooms, code switching from English to Bahasa Melayu still occurs in some ESL classrooms. Hence, the objectives of this study are to investigate the reasons and analyze the functions of code switching among teachers and students in an ESL classroom. The sample comprises three English teachers and forty Form Two students from a secondary school in Kuala Lumpur. Data was obtained from a questionnaire, classroom observations and interviews. The observations were video-taped and the interviews were audio-taped. The data obtained were then transcribed for qualitative and quantitative analyses. Theories on reasons of code switching by Crystal (2001), Cook (2001) and Cristmore (2005); and the theory of functions of code switching by Sert (2005) are adapted for data analyses. The findings of this study indicated that all the teachers and students code-switched to Bahasa Melayu in the ESL classroom. The reasons why teachers and students code switched are to understand certain words better, comprehend the lessons better, ensure that the students are on the same track, make classroom conversations more interesting, use as a short cut to explain tasks and avoid educational inferiority among the students who don’t understand the content taught. This study also revealed that the functions of code switching include topic switch, repetitive or reiteration functions, affective functions, floor-holding, equivalence and conflict control. One implication of this study is that in theory, the teachers disapprove of code switching but in reality, they practice it in the ESL classroom. This study recommends that further research should be done with a bigger sample from both urban and rural schools. Interviews with the officers from the Ministry of Education and principals of schools should also be conducted in order to v obtain a deeper insight into their negative perceptions towards code switching in the ESL classrooms.